Web radio time to sign off?. - Cherry, S.M.
Higher-than-expected royalty rates will force US webcasters to close up shop. The first bad news for Web radio came in February 2002 with a ruling from a copyright arbitration royalty panel (CARP). The panel was set up by the US Copyright Office to satisfy a 1998 law, the Digital Millennium Copyright Act. Its report, which called for even more ruinous rates, was set aside on 21 May by the head of the US Library of Congress, who as overseer of the US Copyright Office has the ultimate authority for setting statutory copyright rates.
Keywords: Digital Millennium Copyright Act; US Copyright Office; US Library of Congress; USA; Web radio; Copyright arbitration royalty panel; Royalty rates; Statutory copyright rates